Co-Administration of PPV23 and Influenza Vaccines in England and Wales: A Study Based on the Royal College of General Practitioners Sentinel Surveillance Network - Carl Selya-Hammer; Douglas Fleming; Yiling Jiang; Hayley Durnall; Sam Keeping; Stuart Carroll (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
Background: Pneumococcal disease is an infection caused by a bacterium called Streptococcus pneumonia which can lead to life-threatening invasive pneumococcal diseases. In the UK, pneumococcal vaccination is targeted at those most at risk of serious disease: infants, older people and those with risk factors. It has been proposed that PPV23 be co-administered with influenza vaccine, during seasonal vaccination to maximize uptake. This study aimed to estimate 1) the UK prevalence of pneumococcal risk co-morbidities 2) corresponding pneumococcal vaccine administration rates 3) rates of vaccination co-administration and 4) frequency of pneumococcal re vaccination. Methods: To gather evidence on current vaccination practice in the UK and to quantify the rates of co-administration of influenza and pneumococcal vaccination, data was collected from general practices in the Royal College of General Practitioners sentinel surveillance network. To estimate the frequency of pneumococcal re vaccination, the records of all persons vaccinated from 2010-2012 were examined and persons were counted according to the number of prior vaccine doses received since 2004. Results: The prevalence rate for COPD was highest amongst the risk groups at 83.56 per 1,000 in 2010 and 79.33 in 2012. The vaccination rate was 6 per 1,000 among risk groups. Patients aged between 65 and 74 years showed the highest rate of vaccination (35 per 1,000), and rates were highest in the immun ocompromised and leukemia sufferers. Co-administration of pneumococcal and influenza vaccines increased sharply from 47% in 2011 to 61% in 2012. Among patients vaccinated against pneumococcal diseases, the proportion who had previously received a pneumococcal vaccination increased from 3 to 9 per 1,000 vaccinations from 2010 to 2012. Conclusion: This study clarifies the current state of pneumococcal vaccination in England and Wales and highlights the need for vaccination coverage rates to be improved in order to prevent more cases of pneumococcal diseases.